Business relationships with East Asia : the European experience - Slater, Jim, 1947-; Strange, Roger (Routledge advances in Asia-Pacific business, 1997)
This volume analyses the business environment in East Asia with reference to trade and investment flows within the region and between East Asia and Europe. Focusing on the two-way flow of management ideas, investment and technology, this study highlights the way in which both sides can benefit.